USE OF INTERACTIVE EDUCATIONAL METHODS IN TEACHING ASTRONOMY - Hotamov, Jaxongir (Физико-технологического образование, 2023)
This at work in universities astronomy course in teaching of education interactive methods used without study classic of the methods efficiency aspects showing given